Biostimulation of a novel native Bacillus strain capable of degrading gasoline - Alkhedir, Ghadeer Mohammed; Abdalla, Mohamed Abdalla Omer; Bilal, Sahar (The Asia Journal of Applied Microbiology, 2024)
The contamination of soil with hydrocarbons is a significant ecological issue worldwide, posing a threat to the ecosystem. Therefore, it is crucial to develop environmentally friendly and effective techniques to eliminate pollutants using biological agents. This study aimed to isolate, characterize, and evaluate bacteria capable of degrading gasoline. Soil samples contaminated with gasoline were collected and diluted up to 10-10. Pure cultures were obtained by streaking dilutions of 10-7, 10-6, and 10-5 on nutrient agar. These pure cultures were then inoculated on a selective medium (Bushnell Haas minerals agar). The isolates were characterized based on their growth patterns using morphological characteristics, optical density measurement, and biochemical tests. As a result, five gasoline-degrading bacteria were identified as B. mojavensis and B. licheniformis. Two biodegradation experiments were conducted using low and high concentrations of gasoline (0.01/10 and 0.001/10 mL, respectively) over a period of 14 days. Furthermore, the bacterial strains were stimulated by adding nitrogen and phosphorus to evaluate their efficiency in degrading gasoline. The results showed that B. mojavensis has the potential to degrade gasoline more effectively than the other isolate. Additionally, the addition of nitrogen minerals enhanced the ability of this isolate to degrade gasoline. Conversely, the performance of B. licheniformis in degrading gasoline was improved with the addition of nitrogen and phosphorus. This study demonstrates the effectiveness of Gram-positive bacteria in gasoline degradation and highlights the potential of the genus B. mojavensis for in situ remediation of gasoline-contaminated soils.